Cone Beam Computed Tomography Evaluation and Surgical Treatment of an Open Apex Case with Biodentine - Ahmed, Fahad; Singh, Mahesh Pratap; Agrawal, Manish; Singh, Kunwar Suhrab; Mansoori, Khushboo; Sethi, Priyank (Journal of Orofacial Research, 2014)
Trauma to the facial region is a common event with injury of teeth. The treatment is aimed at the functional restoration of tooth along with complete biologic healing. Biodentine (Septodont, St Maurdes Fossés, France) introduced in the year 2011. It is a calcium silicate based material and is claimed by the manufacturers as repair of crown and root dentin repair treatment, perforations, resorptions, apexification, and root end fillings. This article presents a case report of conebeam computed tomography (CBCT) diagnosis and surgical management of an open apex case using biodentine as retrograde filling material.